Commentary: Climate change worry among adolescents—on the importance of going beyond the constructive–unconstructive dichotomy to explore coping efforts—a commentary on Sciberras and Fernando (2021). Issue 1 (13th December 2021) - Ojala, Maria
Abstract : This opinion piece comments on Sciberras and Fernando's (2021) article in which an 8‐year longitudinal study is presented. The authors investigate trajectories of climate change worry through adolescence and associations with measures of depression and engagement with news and politics in late adolescence. Their objective is to explore whether climate change worry is a constructive or unconstructive psychological phenomenon. Their conclusion is that it is mainly an adaptive response but, for some groups, such as young people with pre‐existing mental health problems, climate change worry could exacerbate their difficulties. In this commentary, it is argued that since research has found diverse results regarding whether climate worry is adaptive or not, one should perhaps not focus so much on the emotion itself, but rather on how people cope with their worry. Some examples of how young people cope with climate change are presented, and it is argued that taking account of these coping strategies in future longitudinal studies would be beneficial.